Influencing Factor Analysis on the Anomalously Low-Friction Effect in the Block Rock Mass - Liping Li; Jinpeng Wu; Yishan Pan; Jupeng Tang (Advances in Civil Engineering)
According to the instability failure of the deep rock mass, a superposition block model of anomalously low-friction effect was established. The numerical results were compared with the previous experiment, which verifies the feasibility and effectiveness of the simulation. A vertical impact and confining pressure were applied to the superimposed block model, and a horizontal static force was applied to the working block (the third block). This study aimed to determine the influence rules of vertical impact energy, confining pressure, and block lithology on the horizontal displacement of the working block and normal force on the contact surface. The results show that, with the increase of the vertical impact energy, the horizontal residual displacement of the working block increases linearly, and the horizontal displacement amplitude increases by the exponential function. The minimum normal force on the contact surface decreases linearly. As the confining pressure increases, the horizontal residual displacement of the working block decreases logarithmically, and the horizontal displacement amplitude decreases linearly. The minimum normal force on the contact surface increases linearly. The horizontal residual displacement and displacement amplitude of the working block in the coal-rock combination are 1.51 times and 1.63 times of the rock mass, and the minimum normal force of the former is 0.84 times of the latter. Coal-rock combination is more prone to the anomalously low-friction effect than the rock mass.